A Study on the Reuse Intention of E-Commerce Platform Applications: Security, Privacy, Perceived Value, and Trust - Mohamad Yusak Anshori; Denis Fidita Karya; Mira Nirmala Gita (Universitas Airlangga, 2022)
Objective: Security, privacy, perceived value, and trust are essential elements in reusing intention in an e-commerce application. The lower the security, privacy, perceived value, and trust of a consumer will reduce the reuse intention of an e-commerce application because consumers have many choices. This study aims to analyze the relationship between security, privacy, perceived value, and trust in the intention to reuse e-commerce applications. Design/Methods/Approach: The objects of this study are consumers who have made transactions through the Tokopedia application at least once using the purposive sampling technique. The collection method distributes questionnaires online via google form and analyzes them using the Partial Least Square (PLS) method with the SmartPLS 3.3 application. The total number of respondents was 242 people. Findings: The results show that security and privacy had a significant positive effect on perceived value and trust, then perceived value had a significant positive impact on reuse intention. In contrast, the impact of faith on reuse intention was positive but not significant. Originality: This research topic is very important considering the lack of data at Tokopedia beginning of May 2020 was allegedly causing a decline in the number of Tokopedia users. It will become an important reference for many e-commerce in Indonesia, especially e-commerce companies. E-Commerce makes consumers return to use their services, or in this case, it is called the intention to reuse.